Mid- to late Pliocene (3.3–2.6 Ma) global sea-level fluctuations recorded on a continental shelf transect, Whanganui Basin, New Zealand. (1st December 2018) - Grant, G.R.; Sefton, J.P.; Patterson, M.O.; Naish, T.R.; Dunbar, G.B.; Hayward, B.W.; Morgans, H.E.G.; Alloway, B.V.; Seward, D.; Tapia, C.A.; Prebble, J.G.; Kamp, P.J.J.; et al.
Abstract: We present a ∼900 m-thick, mid- (3.3–3.0 Ma) to late Pliocene (3.0–2.6 Ma), shallow-marine, cyclical sedimentary succession from Whanganui Basin, New Zealand that identifies paleobathymetric changes, during a warmer-than-present interval of Earth history, relevant to future climate change. Our approach applies lithofacies, sequence stratigraphy and benthic foraminiferal analyses to two continuously-cored drillholes integrated with new and existing outcrop studies. We construct a depositional model of orbitally-paced, global sea-level changes on a wave-graded continental shelf. Unlike many previous studies, these shelf sediments were not eroded during sea-level lowstands and thus provide the potential to reconstruct the full amplitude of glacial-interglacial sea-level change. Paleobathymetric interpretations are underpinned by analysis of extant benthic foraminiferal census data and a statistical correlation with the distribution of modern taxa. In general, water depths derived from foraminiferal Modern Analogue Technique (MAT), are consistent with variability recorded by lithofacies. The inferred sea-level cycles co-vary with a qualitative climate record reconstructed from a census of extant pollen and spores, and a modern temperature relationship. A high-resolution age model is established using magnetostratigraphy constrained by biostratigraphy, and the dating and correlation of tephra. This integrated chronostratigraphy allows the recognition of 23 individual sedimentary cycles, that are correlated across the paleo-shelf and a possible "one-to-one" relationship is made to deep-ocean benthic oxygen isotope (δ 18 O) records. In general water depth changes were paced by ∼20 kyr duration between 3.3 and 3.0 Ma, after which cycle duration is ∼40 kyr during the late Pliocene (3.0–2.6 Ma). This record provides a future opportunity to evaluate the amplitude and frequency of global, Pliocene glacio-eustatic sea-level change, independent of the global benthic δ 18 O record. Highlights: First continuous Pliocene shallow-marine record of orbitally-paced waterdepth change. Mid-Pliocene (3.3–3.0 Ma) displays 20 kyr precession-paced cyclicity. Late Pliocene (3.0–2.6 Ma) displays 41 kyr obliquity paced cyclicity. Potential to constrain global sea-level amplitude and frequency at glacial cyclicity.